PELESTARIAN KAWASAN PECINAN KEMBANG JEPUN KOTA SURABAYA BERDASARKAN PERSEPSI MASYARAKAT - Kartika Eka Sari; Antariksa .; Eddi Basuki Kurniawan (Dimensi: Journal of Architecture and Built Environment, 2011)
This research’s objective are to identify physical, economic and culture characteristic of Kembang Jepun, analyze potention and issue related to Kembang Jepun’s preservation and develop Kembang Jepun’s preservation. Local communities’s perception is use to analyze cultural meaning of Kembang Jepun, especially building’s age, aesthetic, scarcity, originality, strengthen the cultural meaning and area’s image. Based on IPA (Importance Performance Analysis) method, most priority for cultural meanings (scale 3) in determining building’s preservation strategy in Kembang Jepun is to strengthen the cultural meaning (the original bulding’s function in maintained), Area’s image (building;s character is repeated dominantly, community’s landmark and the function is suitable with Kembang Jepun’s character). Cultural meaning that have scale 2 are aesthetic, scarcity and cultural meaning that have scale 1 are building’s age and originality. Scales of cultural meanings (1 to 3) is combine with buildings’s value and the result are: 11 ancient building for preservation’s strategy, 34 ancient buildings for conservation’s strategy, 27 ancient buildings for revitalitation’s strategy and 17 ancient buildings for rehabilitation’s strategy.